The duke knows best ebook - Ashford, Jane (Duke's Sons, 2017)
They're wrong for each other, for all the right reasons... Lord Randolph Gresham has come to London for one reason only—to find a suitable wife. Verity Sinclair may be intelligent, beautiful, and full of spirit, but her father knows a secret about Randolph that makes her entirely unsuitable as his bride. Not right for him at all, never, not a chance. Verity knows that Lord Randolph lives in a country parish, and she wants nothing more than to escape to town. He may be fascinating, attractive, rich, and the son of a duke, but she'll never marry him, nor will she talk to him, flirt with him, walk with him, or dine with him. She'll sing a duet with him, but only this one time, and only because everyone insists. But one duet invariably leads to another. The Duke's Sons Series: Heir to the Duke (Book 1) What the Duke Doesn't Know (Book 2) Lord Sebastian's Secret (Book 3) Nothing Like a Duke (Book 4) The Duke Knows Best (Book 5)